2000
DOI: 10.5935/0305-7518.20000065
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprophylaxis against leprosy: expectations and methodology of a trial

Abstract: Because of the great efficacy of multidrug therapy (MDT), it had been hoped that the widespread use of MDT would bring about a rapid decrease of the incidence of leprosy. To the present, a decrease of incidence has not been observed, possibly because of the long incubation period of the disease, and because general implementation of MDT is still recent. Other reasons, such as environmental sources of infection or the role of healthy carriers in transmitting Mycobacterium lepr ae, cannot be excluded. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…All people living in the same household as an index case and sharing the same kitchen will be considered as household contacts. To be certain that transmission of the organisms from the index case cannot occur once the prophylaxis has been administered, rifampicin will be given two months after diagnosis of the index case (Vijayakumaran et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…All people living in the same household as an index case and sharing the same kitchen will be considered as household contacts. To be certain that transmission of the organisms from the index case cannot occur once the prophylaxis has been administered, rifampicin will be given two months after diagnosis of the index case (Vijayakumaran et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados dessas experiências operacionais não possibilitam avaliar a eficácia dessa intervenção e são difíceis de serem extrapolados para outros contextos 67,68 . Um ensaio preventivo, aleatório, placebo controlado, para avaliar a efetividade de dose única de rifampicina em contatos domiciliares de pacientes com hanseníase vem sendo planejado para ser conduzido em múltiplas regiões da Índia 69 . Chama a atenção o tamanho da amostra requerido de 15.000, calculado considerando-se a eficácia da quimioprofilaxia de 50%, em incidência anual de 2 casos por 1.000 contatos (poder estatístico de 90% e alfa de 95%), e seguimento de 5 anos.…”
Section: Quimioprofilaxiaunclassified
“…Various chemoprophylaxis trials have been conducted to determine whether pre-emptive "treatment" can interrupt leprosy transmission and reduce disease prevalence. These studies have demonstrated a significant benefit to treating non-diseased individuals, although each has reported a different magnitude and length of protection (Daulako 1999, Tin 1999, Diletto et al 2000, Nguyen et al 2000, Vijayakumaran et al 2000, Moet et al 2004, Bakker et al 2005, Smith 2008). The findings of the heralded COLEP trial, which was conducted on approximately 20,000 contacts of new cases in north-west Bangladesh, showed a protective effect associated with single-dose rifampicin (RIF) treatment of 57% in household and other contacts (Moet et al 2008a).…”
Section: Resultsmentioning
confidence: 99%